(untitled) (The International Journal for Scientific Research, 2023)
This study aimed to identify the effect of adding local ginger powder at a rate of 5, 7 and 10% and fresh local ginger at a rate of 7% on the numbers of pathogenic microbial in chicken meat discs manufactured in a laboratory and preserved under freezing conditions -12 °C for 15, 30 and 60 days. The bacteriological analysis conducted on the chicken frozen tablets included the total number of bacteria, coliform bacteria, Psychrotrophic bacteria, Staphylococcus aureus bacteria and numbers of fungi and yeasts. The results of bacteriological analysis indicated a decrease in most types of the numbers of pathogenic microbes in chicken meat discs preserved under freezing conditions at -12°C when adding concentrations of 5, 7 and 10% of ginger powder and fresh ginger at a rate of 7%. Where the inhibitory effect was on the total numbers of bacteria, coliform bacteria Psychrotrophic bacteria and Staphylococcus aureus bacteria, the number of fungi and yeasts at a concentration of 5% of dry ginger powder during the 15day storage period where a decrease was observed from 6.166, 4.873, 4.477, 5.493 and 4.814 log10 cfu/g to 5.985, 3.982, 2.229, 4.926 and 4.642 log10 cfu/g respectively. The resulted showed an increase in the frozen storage period to 30 days the microbial content had a significant effect at a significant level of P < 0.05 as it was in the control treatment 5.655, 4.362, 5.638, 5.022 and 4.892 log10 cfu/g when adding dry ginger at a concentration of 5%, the numbers were 5.474, 3.741, 2.162, 4.527 and 5.031 log10 cfu/g respectively. It was observed that the total number of bacteria, coliform bacteria, Psychrotrophic bacteria, Staphylococcus aureus bacteria and numbers of fungi and yeasts increased in the control treatment at 60 day of frozen storage were 4.963, 4.537, 5.827, 4.676 and 4.472 log10 cfu/g, while when adding dry ginger at a concentration of 5%, inconstancy was seen in most of the pathogenic microbial numbers were 4.782, 3.692, 2.316, 3.746 and 4.738 log10 cfu/g respectively. The results also showed a decrease in most of the numbers of pathogenic bacteria by adding concentrations of 7 and 10% of dry ginger powder during 60 days on the total number of bacteria from 4.409 to 4.603log10 cfu/g and coliform bacteria from 3.978 to 3.833 log10cfu/g and Psychrotrophic bacteria from 2.116 to 1.151 log10cfu/g and Staphylococcus aureus bacteria from 4.424 and 3.967 log10 cfu/g and numbers of fungi and yeasts from 3.636 to 2.742 log10 cfu/g respectively. Also, the results showed that adding a concentration of 7% of fresh ginger during the storage period of 60 days had the highest inhibitory effect on the total numbers of bacteria, coliform bacteria Psychrotrophic bacteria and Staphylococcus aureus bacteria, the number of fungi and yeasts which recorded 4.084, 3.551, 1.962, 4.028 and 2.768 log10 cfu/g respectively compared to the control sample, which were 4.963, 4.537, 5.827, 4.472 and 4.676 log10 cfu/g respectively.